CoSnO3 / BiVO4 photoanode, preparation method and application of CoSnO3 / BiVO4 photoanode in preparation of hydrogen peroxide

CoSn(OH)6 powder was prepared by co-precipitation method and hydrothermal method, and CoSnO3/BiVO4 photocatalytic electrodes were prepared in combination with electrodeposition method and spin coating method, which solved the problems of complex and high cost of photocatalytic materials preparation in the prior art, and achieved efficient and low-cost preparation of hydrogen peroxide.

CN119571382AActive Publication Date: 2025-03-07XI AN JIAOTONG UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411772499.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing photoelectrocatalytic materials require complex process flow and high-cost raw materials when preparing hydrogen peroxide, and have high operating requirements, making it difficult to achieve large-scale industrial production.

Method used

CoSn(OH)6 powder was prepared by co-precipitation method and hydrothermal method, and a dense and uniform BiVO4 catalyst layer and CoSnO3 catalyst layer were prepared on the surface of the FTO substrate by combining electrodeposition method and spin coating method to form a CoSnO3/BiVO4 photoelectro-catalytic electrode.

Benefits of technology

The preparation of photoelectromethods with low cost, simple process, good electrochemical stability and catalytic performance is realized, the photocurrent density of BiVO4 is improved, and high selectivity and high yield are shown in the preparation of hydrogen peroxide by oxidation of di-electron water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571382A_ABST
    Figure CN119571382A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water photoelectrolysis materials, and relates to a CoSnO3 / BiVO4 photoanode, a preparation method and application of the CoSnO3 / BiVO4 photoanode in preparation of hydrogen peroxide. 2, adding the solution A into a Co source and a Sn source through a coprecipitation method, and then hydrothermally preparing CoSn (OH) 6 powder; 3, dissolving a Bi source in a solvent B to prepare a Bi precursor solution, and introducing the Bi source on the conductive substrate through an electro-deposition method; 4, dissolving a V source in a solvent C, introducing the V source on the conductive substrate by using a spin coating device, and heating and calcining in a high-temperature heating device to prepare a photoanode BiVO4 layer; and 5, introducing CoSn (OH) 6 on the conductive substrate by a spin-coating method, and heating and calcining in a high-temperature heating device to finally obtain the CoSnO3 / BiVO4 photoelectrocatalysis electrode. The prepared photoelectric catalyst can effectively improve the photocurrent of original BiVO4, and has high selectivity and high yield in the reaction of preparing hydrogen peroxide through two-electron water oxidation, so that the cost of preparing hydrogen peroxide through photoelectric catalysis can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectrolytic water materials and relates to a CoSnO3 / BiVO4 photoanode, a preparation method and application thereof in preparing hydrogen peroxide. Background Art

[0002] As an important chemical oxidant and medical disinfectant, hydrogen peroxide (H2O2) has broad application prospects in environmental protection, medical health, chemical synthesis and other fields. Traditional methods for preparing hydrogen peroxide mainly rely on industrial chemical processes, including chemical reactions of oxidants and reductants. However, these methods usually require high temperature and high pressure conditions, produce a large number of by-products, and cause significant pollution to the environment. In order to solve these problems of traditional preparation methods, photoelectrocatalytic technology has emerged in the field of hydrogen peroxide preparation. Photoelectrocatalytic technology is a new green synthesis method that integrates photocatalysis and electrochemical reactions. It uses visible light or ultraviolet light to excite electrons on the surface of the catalyst, thereby promoting the redox reaction. In particular, the photoelectrocatalytic preparation of hydrogen peroxide has the advantages of high efficiency, environmental friendliness and controllability, and has become one of the current research hotspots.

[0003] Among many materials, BiVO4 has a higher light utilization rate. Compared with TiO2, which can only respond in the ultraviolet light band, BiVO4 can respond in the visible light band (visible light accounts for 43% of sunlight). Therefore, bismuth vanadate has always played a very important role in photoelectrocatalytic research. However, due to its slow reaction kinetics, poor conductivity, and high electron-hole pair recombination rate, the actual photocurrent level of the BiVO4 photoanode is far lower than its theoretical expectations. Therefore, in the field of photoelectrocatalysis, how to modify the photoelectrocatalytic performance of bismuth vanadate and improve its photocurrent density and selectivity of target products has become an important part of research progress in recent years. Researchers often improve its carrier mobility and conductivity through morphology control, doping, and composite formation of heterojunctions, and ultimately achieve the purpose of improving photoelectrocatalytic activity.

[0004] The unique octahedral structure of perovskite-structured metal oxides gives it excellent photoelectrochemical properties. It also has high specific surface area and pore structure. In the catalytic reaction process, it provides channels for the catalytic reaction substances to enter and the products to leave. The pore structure can also promote the diffusion and transmission of the reaction substances, thereby improving the efficiency of the catalytic reaction. The CoSnO3 powder prepared by the coprecipitation method has the characteristics of simple structure, high stability, and fast electron transfer rate. At the same time, CoSnO3, as a mixed transition metal oxide, has two different metal cations. Cobalt ions have been shown to promote the oxidation of water to generate hydrogen peroxide, and tin-based catalysts often play an important role in electrocatalytic applications. After the composite of CoSnO3 and BiVO4, the excellent visible light excitation ability of BiVO4 can be utilized, and the electron transfer ability of the photoelectrocatalytic material can be greatly improved through CoSnO3, reducing the composite consumption of photogenerated carriers in the catalytic material, so that more photogenerated carriers can participate in the redox reaction on the surface of the photoelectrocatalytic material, thereby promoting the photoelectrocatalytic reaction.

[0005] Invention CN110468428A discloses a semiconductor anode material for photoelectrocatalytically preparing hydrogen peroxide and a preparation method thereof. TiO2 nanorods are grown on FTO conductive glass, and Co3O4 nanoparticles are loaded thereon to finally obtain a Co3O4 / TiO2 composite photoelectroanode material. The preparation includes three steps: preparing a TiO2 nanorod precursor solution, preparing TiO2 nanorods grown on FTO conductive glass by a hydrothermal method, and obtaining the Co3O4 / TiO2 composite photoelectroanode material by a drip coating method.

[0006] Invention CN111979561B discloses a SnO x / BiVO4 electrode and its preparation method and application in photoelectrocatalytic hydrogen peroxide synthesis. The method first dissolves stannous chloride in a mixed solution of ethylene glycol methyl ether and acetylacetone, and after ultrasonication and standing, spin-coats it on the surface of bismuth vanadate photoelectrode, and then anneals it in an argon atmosphere to form a tin oxide passivation layer on the surface to obtain SnO x / BiVO4 electrode. The present invention can reduce the light corrosion of the surface bismuth vanadate, increase the stability of bismuth vanadate, and improve the separation efficiency of electrons and holes by loading a tin oxide film passivation layer on the surface of bismuth vanadate.

[0007] Invention CN118477653A discloses a WO3 / FeOOH heterojunction composite film and its preparation method and application, which relates to the field of thin film material preparation. The WO3 / FeOOH heterojunction composite film provided by the present invention is composed of a tungsten trioxide film and iron oxyhydroxide in-situ grown on the surface of the tungsten trioxide film, and the tungsten trioxide film is in-situ grown on the surface of the substrate. In the present invention, WO3 and FeOOH are both semiconductor photocatalytic materials that respond to visible light. WO3 and FeOOH are coupled to form a WO3 / FeOOH heterojunction, which has excellent photoelectric catalytic performance.

[0008] Invention CN118345379A discloses a method for improving the photoelectrocatalytic synthesis of hydrogen peroxide by organic polymers, using a photoelectrochemical cell comprising a photocathode; the photocathode is an electrode of an organic copolymer semiconductor catalyst having a light response; the cathode is coupled with an anode to form a photocathode-anode photoelectrochemical system, the photocathode is in contact with at least one reactant of an oxygen-containing mediator dissolved in a continuous phase; the continuous phase comprises an electrolyte and a neutral solvent containing water, and the reactant of the oxygen-containing mediator is an oxygen-containing gas; under the conditions of light and a voltage below 0 to 3V, the photocathode reduces the oxygen in the oxygen-containing gas in the continuous phase into hydrogen peroxide.

[0009] The above invention method grows titanium dioxide nanorods on FTO conductive glass by a hydrothermal method and loads cobalt oxide nanoparticles to achieve efficient photoelectrocatalytic activity. Alternatively, stannous chloride is spin-coated on the surface of a bismuth vanadate electrode and annealed in an argon atmosphere to form a tin oxide passivation layer, which effectively improves the stability of bismuth vanadate and the separation efficiency of electrons and holes. Alternatively, a heterojunction composite film composed of tungsten trioxide and iron oxyhydroxide is coupled with tungsten oxide and iron oxyhydroxide to improve the visible light response and photoelectrocatalytic performance of the composite material. Alternatively, an organic polymer photocathode-anode photoelectrochemical system is proposed to reduce oxygen to generate hydrogen peroxide under light and low voltage, demonstrating the application potential of organic semiconductors in the field of photoelectrocatalysis.

[0010] However, the preparation of these catalytic electrodes in the prior art requires a lot of pre-operation and complex process flow, which requires sophisticated instruments and equipment and high-cost raw materials, and also places high demands on the operator's operating skills. In addition, most experiments do not involve perovskite-type metal oxide materials that are more stable, more conductive, and more catalytically active.

[0011] Therefore, seeking a low-cost, simple process, and electrochemically stable and catalytic performance catalyst preparation method for the composite of perovskite metal oxide materials and BiVO4 is crucial for further research on the industrialization of photoelectrocatalytic preparation of hydrogen peroxide. Summary of the invention

[0012] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a CoSnO3 / BiVO4 photoanode, comprising the following steps:

[0013] Step s1, cleaning the conductive substrate to remove impurities on the surface of the conductive substrate;

[0014] Step s2, adding solution A to the Co source and Sn source solutions by co-precipitation method to prepare catalyst slurry, and then transferring the slurry to a chemical reaction device for hydrothermal preparation of CoSn(OH)6 powder;

[0015] Step s3, dissolving a Bi source in solvent B to prepare a Bi precursor solution, and introducing the Bi source onto the conductive substrate treated in step s1 by electrodeposition;

[0016] Step s4, dissolving the V source in solvent C, and then introducing the V source by spin coating on the conductive substrate treated in step s3 using a spin coating device and heating and calcining in a high temperature heating device to prepare a photoanode BiVO4 layer;

[0017] Step s5, introducing CoSn(OH)6 on the conductive substrate treated in step s4 by spin coating using a spin coating device and heating and calcining in a high temperature heating device to finally obtain a CoSnO3 / BiVO4 photoelectrocatalytic electrode;

[0018] Solution A includes: one or more of sodium hydroxide, potassium hydroxide, and calcium hydroxide;

[0019] Solvent B includes: one or more of glacial acetic acid, nitric acid, sulfuric acid, hydrochloric acid, oxalic acid, and deionized water;

[0020] Solvent C includes: one or more of ethylene glycol, ethanol, methanol, isopropanol, and deionized water.

[0021] Preferably, the Co source includes: one or more of cobalt chloride hexahydrate, cobalt sulfate heptahydrate, hydrated cobalt carbonate, and cobalt nitrate hexahydrate; the Sn source includes: one or more of tin chloride dihydrate, anhydrous stannous chloride, tin sulfate, stannous sulfate, stannous carbonate, and stannous oxalate; the Bi source includes: one or more of bismuth nitrate pentahydrate, bismuth subcarbonate dihydrate, and bismuth sulfate; the V source includes: one or more of vanadium acetylacetonate, ammonium metavanadate, and vanadium pentoxide.

[0022] Preferably, the conductive substrate includes: fluorine-doped silicon dioxide conductive glass FTO, indium tin oxide transparent conductive film glass ITO, and a stainless steel plate.

[0023] Preferably, in step s2, the chemical reaction apparatus includes: a reactor, an autoclave, a stirred reactor, a continuous flow reactor, a microreactor, a batch reactor, a fixed bed reactor, a fluidized bed reactor;

[0024] In step s4 and step s5, the high temperature heating device includes: a muffle furnace, a tube furnace, a box furnace, a vacuum furnace, an atmosphere furnace, a resistance furnace, and an induction furnace.

[0025] In step s4 and step s5, the spin coating device includes: a glue spreader, a spin coater, a glue spinner, a spin coater, a spin film coater, a spin coating machine, a spin coater, and a vacuum coating machine.

[0026] Preferably, in step s1, the cleaning step comprises: using deionized water, acetone, isopropanol and ethanol in sequence to ultrasonically bathe the conductive substrate for 5 to 20 minutes; the sizes of the conductive substrate include: 1cm*1cm, 1cm*2cm, 2cm*2cm, 2cm*3cm.

[0027] Preferably, in step s2, the stirring speed of the coprecipitation method is 100-800 rpm, the stirring time is 10 min-24 h, the hydrothermal time is 6-18 h, and the hydrothermal temperature is 120-200°C.

[0028] Preferably, in step s3, the electrodeposition conditions include: applying an external bias voltage of 0.5V to 2.5V vs. Ref for 10min to 2h;

[0029] Among them, in the three electrodes of electrodeposition, the counter electrode includes: one of a carbon counter electrode and a platinum counter electrode; the reference electrode includes: one of a saturated Hg / Hg2SO4 electrode, a saturated Ag / AgCl electrode, a saturated Hg / HgO electrode, and a calomel electrode; and the working electrode is a conductive substrate.

[0030] Preferably, in step s4, the temperature of the high temperature heating device is set to 350-500° C., the heating rate is 5-10° C. / min, and the calcination time is 1-4 hours;

[0031] In step s5, the temperature of the high temperature heating device is set to 250-400° C., the heating rate is 5-10° C. / min, and the calcination time is 1-4 hours.

[0032] The present invention also discloses a CoSnO3 / BiVO4 photoanode, wherein the CoSnO3 / BiVO4 photoanode is prepared by adopting the preparation method of the CoSnO3 / BiVO4 photoanode.

[0033] The present invention also discloses an application of a CoSnO3 / BiVO4 photoanode in preparing hydrogen peroxide. The application adopts the CoSnO3 / BiVO4 photoanode to prepare hydrogen peroxide.

[0034] The beneficial effects of the present invention are:

[0035] The present invention prepares CoSn(OH)6 powder by coprecipitation and hydrothermal method, and prepares dense and uniform BiVO4 catalyst layer and CoSnO3 catalyst layer on the surface of FTO substrate by combining electrodeposition and spin coating method, so as to form a composite photoelectrocatalytic anode material with excellent catalytic activity and strong corrosion resistance. After multiple photoelectrochemical tests, the catalyst does not obviously fall off and has good light transmittance. In addition, all raw materials used in the present invention have the advantages of low price, abundant yield, easy acquisition, etc., and low equipment requirements in the preparation process, easy operation, simple preparation method, and industrial large-scale electrode preparation can be realized. Therefore, the photoelectrocatalyst prepared by the present invention can effectively improve the photocurrent of the original BiVO4 itself, and can have high selectivity and high yield in the reaction of preparing hydrogen peroxide by two-electron water oxidation, with the highest yield of 0.449 μmol min -1 cm -2 The Faraday efficiency reaches 79.23%, and it has excellent stability. The preparation method is simple and easy to control, which can effectively reduce the cost of photoelectrocatalytic preparation of hydrogen peroxide and promote the popularization and application of this technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a scanning electron microscope morphology image of the electrode samples of Example 1 and Example 2 of a CoSnO3 / BiVO4 photoanode, a preparation method and its application in preparing hydrogen peroxide of the present invention;

[0037] Figure 2 is a transmission electron microscope morphology image of the catalyst sample of Example 2 of the present invention;

[0038] Figure 3 is the XRD diagram of the catalyst samples of Examples 1-4 of the present invention;

[0039] Figure 4 1 is the XPS graph of the catalyst samples of Example 1 and Example 2 of the present invention;

[0040] Figure 5 It is a linear sweep voltammetric curve test diagram of Examples 1-4 of the present invention;

[0041] Figure 6 Graph showing the photoelectrocatalytic Faraday efficiency and hydrogen peroxide yield of Example 2 of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] This embodiment aims to provide a CoSnO3 / BiVO4 photoanode and a preparation method thereof and an application in the photoelectrocatalytic preparation of hydrogen peroxide. The equipment requirements are low, the process is simple and the cost is low in the electrolysis of water, which further expands the selection range of photoelectrocatalysts, reduces the cost of catalyst preparation and improves the photoelectrocatalytic efficiency.

[0044] Reference Figures 1 to 6 This embodiment provides a CoSnO3 / BiVO4 photoanode and a preparation method thereof and an application thereof in photoelectrocatalytic preparation of hydrogen peroxide, specifically comprising the following steps:

[0045] Step s1, cleaning the conductive substrate to remove impurities on the surface of the conductive substrate;

[0046] Step s2, adding solution A to the Co source and Sn source solutions by co-precipitation method to prepare catalyst slurry, and then transferring the slurry to a chemical reaction device for hydrothermal preparation of CoSn(OH)6 powder;

[0047] Step s3, dissolving a Bi source in a solvent B to prepare a Bi precursor solution, and introducing the Bi source onto a conductive substrate by an electrodeposition method;

[0048] Step s4, dissolving the V source in solvent C, and then introducing the V source on the conductive substrate treated in s3 by spin coating using a spin coating device and heating and calcining in a high temperature heating device to prepare a photoanode BiVO4 layer;

[0049] Step s5, introducing CoSn(OH)6 on the conductive substrate treated in step s4 by spin coating using a spin coating device and heating and calcining in a high temperature heating device to finally obtain a CoSnO3 / BiVO4 photoelectrocatalytic electrode;

[0050] Furthermore, in the step s1, the catalyst substrate is made of FTO with good light transmittance and conductivity, and has a size of 2cm*3cm.

[0051] Furthermore, in step s1, the cleaning step is to use deionized water, acetone, isopropanol and ethanol in sequence to ultrasonically bath the FTO for 10 minutes.

[0052] Furthermore, in step s2, the cobalt source is cobalt chloride hexahydrate, and the tin source is tin chloride dihydrate.

[0053] Furthermore, in step s2, tin chloride dihydrate and cobalt chloride hexahydrate are respectively dissolved in a mixed solvent of 30 mL of ethanol and 30 mL of deionized water, and 10 mL of sodium hydroxide (2M) solution is added dropwise to the tin chloride solution under stirring conditions. Then, cobalt chloride solution is added under stirring conditions to obtain a blue-purple suspension mixture, and stirring is continued for 30 min-24 h.

[0054] Furthermore, in step s3, the Bi source is bismuth nitrate pentahydrate (Bi(NO3)3·5H2O).

[0055] Furthermore, in step s4, the V source is vanadium acetylacetonate.

[0056] Furthermore, in step s2, the stirring speed of the coprecipitation method is 600 rpm, and the stirring time is 30 min to 24 h.

[0057] Furthermore, in step s2, cobalt chloride hexahydrate is used as the cobalt source and tin chloride dihydrate is used as the tin source.

[0058] Furthermore, in step s2, the hydrothermal time is 10 to 12 hours, and the hydrothermal temperature is 150 to 180°C.

[0059] Furthermore, in step s3, one of the counter electrodes of the three electrodes is a platinum counter electrode; the reference electrode is a saturated Hg / Hg2SO4 electrode; and the working electrode is a conductive substrate. The electrodeposition condition is to apply an external bias voltage of 2V to 2.2V vs. Ref for 1 hour.

[0060] Furthermore, in step s4, the amount of each drop in the spin coating method is 50 μL, the total drop is 3 times, the spin coating speed is 4000 rpm, the spin coating acceleration is 800 rpm / s, and the spin coating time is 30 s.

[0061] Furthermore, in step s4, the temperature of the muffle furnace is set to 450° C., the heating rate is 5° C. / min, and the calcination time is 2 h.

[0062] Furthermore, in the step s4, the amount of each drop in the spin coating method is 50 μL, the total drop is 1 time, the spin coating speed is 4000 rpm, the spin coating acceleration is 800 rpm / s, and the spin coating time is 30 s.

[0063] Furthermore, in step s5, the temperature of the muffle furnace is set to 300° C., the heating rate is 5° C. / min, and the calcination time is 2 h.

[0064] Example

[0065] This embodiment provides a CoSnO3 / BiVO4 photoanode and a preparation method thereof and an application thereof in photoelectrocatalytic preparation of hydrogen peroxide, comprising the following steps:

[0066] s1; cleaning the conductive substrate to remove impurities on the surface of the conductive substrate;

[0067] s2; adding solution A to the Co source and Sn source solutions by coprecipitation to prepare a catalyst slurry, and then transferring the slurry to a chemical reaction device for hydrothermal preparation of CoSn(OH)6 powder;

[0068] s3; dissolving a Bi source in a solvent B to prepare a Bi precursor solution, and introducing the Bi source onto a conductive substrate by an electrodeposition method;

[0069] s4; dissolving the V source in solvent C, and then introducing the V source on the conductive substrate treated in s3 by spin coating using a spin coating device and heating and calcining in a high temperature heating device to prepare a photoanode BiVO4 layer;

[0070] s5; introducing CoSn(OH)6 by spin coating on the conductive substrate treated in s4 using a spin coating device and heating and calcining in a high temperature heating device to finally obtain a CoSnO3 / BiVO4 photoelectrocatalytic electrode;

[0071] Specific examples are given below to further illustrate the present invention:

[0072] Embodiment 1:

[0073] 1) FTO cleaning

[0074] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface, so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0075] 2) Introducing Bi source by electrodeposition

[0076] Bi source was introduced on the conductive fluorine-doped tin oxide (FTO) coated glass substrate by electrodeposition. 8mmol Bi(NO3)3·5H2O was dissolved in 50mL aqueous solution containing 16mL acetic acid (99%) and 1.6mL concentrated HNO3 (70wt%) to prepare 0.2M bismuth precursor solution. A three-electrode electrolytic cell was constructed using a Pt counter electrode, a saturated Hg / Hg2SO4 reference electrode, and a cleaned FTO, and an external bias of 2.11V vs.Ref was applied for 1h; the obtained bismuth precursor film was rinsed with ultrapure water and dried naturally at room temperature.

[0077] 3) Introduce V source by spin coating and calcination

[0078] In order to convert the bismuth precursor film into BiVO4 film, the V source was introduced by spin coating. Isopropanol was used as a solvent to prepare a 0.05M vanadium acetylacetonate solution, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL of vanadium acetylacetonate solution was evenly added each time for spin coating, and a total of 3 spin coatings were performed; after drying at room temperature, annealing was performed at 450℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0079] Embodiment 2:

[0080] 1) FTO cleaning

[0081] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface, so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0082] 2) Preparation of CoSn(OH)6 powder by coprecipitation method

[0083] CoSn(OH)6 powder was prepared by coprecipitation. 1.128 g SnCl4·2H2O (0.005 mol) and 1.1901 g CoCl2·6H2O (0.005 mol) was dissolved in a mixed solvent of 30 mL of ethanol and 30 mL of deionized water to obtain a transparent solution; NaOH (2 M) solution was added dropwise to the tin chloride solution under magnetic stirring. During this process, Sn(OH)4 was precipitated first. When NaOH was continuously added, the white precipitate dissolved to form an aqueous solution of Na2Sn(OH)6, and the pH value of the solution was controlled above 12; then cobalt chloride solution was added under magnetic stirring to obtain a blue-purple suspension mixture; after stirring for 10 hours, the formed suspension was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and maintained at 180°C for 12 hours; after the autoclave was naturally cooled to room temperature, the precipitate obtained by suction filtration was thoroughly washed several times with anhydrous ethanol and deionized water, and the precipitate was placed in a vacuum drying oven at 80°C and dried for 12 hours, and the precursor CoSn(OH)6 was obtained after grinding.

[0084] 3) Introducing Bi source by electrodeposition

[0085] Bi source was introduced on the conductive fluorine-doped tin oxide (FTO) coated glass substrate by electrodeposition. 8mmol Bi(NO3)3·5H2O was dissolved in 50mL aqueous solution containing 16mL acetic acid (99%) and 1.6mL concentrated HNO3 (70wt%) to prepare 0.2M bismuth precursor solution. A three-electrode electrolytic cell was constructed using a Pt counter electrode, a saturated Hg / Hg2SO4 reference electrode, and a cleaned FTO, and an external bias of 2.11V vs.Ref was applied for 1h; the obtained bismuth precursor film was rinsed with ultrapure water and dried naturally at room temperature.

[0086] 4) Introduce V source by spin coating and calcination

[0087] In order to convert the bismuth precursor film into BiVO4 film, the V source was introduced by spin coating. Isopropanol was used as a solvent to prepare a 0.05M vanadium acetylacetonate solution, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL of vanadium acetylacetonate solution was evenly added each time for spin coating, and a total of 3 spin coatings were performed; after drying at room temperature, annealing was performed at 450℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0088] 5) Spin coating to introduce CoSn(OH)6 and calcination

[0089] CoSn(OH)6 was also introduced by spin coating to complete the composite of CoSnO3 and BiVO4. The annealed film was rinsed with ultrapure water to remove excess V2O5 on the surface; 0.1MCoSn(OH)6 solution was prepared with ethanol as a solvent, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL CoSn(OH)6 solution was evenly dripped for spin coating; after drying at room temperature, annealed at 300℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0090] Embodiment 3:

[0091] 1) FTO cleaning

[0092] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface, so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0093] 2) Preparation of CoSn(OH)6 powder by coprecipitation method

[0094] CoSn(OH)6 powder was prepared by coprecipitation. 1.128 g SnCl4·2H2O (0.005 mol) and 1.1901 g CoCl2·6H2O (0.005 mol) was dissolved in a mixed solvent of 30 mL of ethanol and 30 mL of deionized water to obtain a transparent solution; NaOH (2 M) solution was added dropwise to the tin chloride solution under magnetic stirring. During this process, Sn(OH)4 was precipitated first. When NaOH was continuously added, the white precipitate dissolved to form an aqueous solution of Na2Sn(OH)6, and the pH value of the solution was controlled above 12; then cobalt chloride solution was added under magnetic stirring to obtain a blue-purple suspension mixture; after stirring for 30 minutes, the formed suspension was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and maintained at 180°C for 12 hours; after the autoclave was naturally cooled to room temperature, the precipitate obtained by suction was thoroughly washed several times with anhydrous ethanol and deionized water, and the precipitate was placed in a vacuum drying oven at 80°C and dried for 12 hours, and the precursor CoSn(OH)6 was obtained after grinding.

[0095] 3) Introducing Bi source by electrodeposition

[0096] Bi source was introduced on the conductive fluorine-doped tin oxide (FTO) coated glass substrate by electrodeposition. 8mmol Bi(NO3)3·5H2O was dissolved in 50mL aqueous solution containing 16mL acetic acid (99%) and 1.6mL concentrated HNO3 (70wt%) to prepare 0.2M bismuth precursor solution. A three-electrode electrolytic cell was constructed using a Pt counter electrode, a saturated Hg / Hg2SO4 reference electrode, and a cleaned FTO, and an external bias of 2.11V vs.Ref was applied for 1h; the obtained bismuth precursor film was rinsed with ultrapure water and dried naturally at room temperature.

[0097] 4) Introduce V source by spin coating and calcination

[0098] In order to convert the bismuth precursor film into BiVO4 film, the V source was introduced by spin coating. Isopropanol was used as a solvent to prepare a 0.05M vanadium acetylacetonate solution, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL of vanadium acetylacetonate solution was evenly added each time for spin coating, and a total of 3 spin coatings were performed; after drying at room temperature, annealing was performed at 450℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0099] 5) Spin coating to introduce CoSn(OH)6 and calcination

[0100] CoSn(OH)6 was also introduced by spin coating to complete the composite of CoSnO3 and BiVO4. The annealed film was rinsed with ultrapure water to remove excess V2O5 on the surface; 0.1MCoSn(OH)6 solution was prepared with ethanol as a solvent, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL CoSn(OH)6 solution was evenly dripped for spin coating; after drying at room temperature, annealed at 300℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0101] Embodiment 4:

[0102] 1) FTO cleaning

[0103] Deionized water, acetone, isopropanol and ethanol were used to ultrasonically bath FTO for 10 min in sequence to remove impurities on the FTO surface, so that the film could evenly cover the entire FTO surface during hydrothermal in situ growth.

[0104] 2) Preparation of CoSn(OH)6 powder by coprecipitation method

[0105] CoSn(OH)6 powder was prepared by coprecipitation. 1.128 g SnCl4·2H2O (0.005 mol) and 1.1901 g CoCl2·6H2O (0.005 mol) was dissolved in a mixed solvent of 30 mL of ethanol and 30 mL of deionized water to obtain a transparent solution; NaOH (2 M) solution was added dropwise to the tin chloride solution under magnetic stirring. During this process, Sn(OH)4 was precipitated first. When NaOH was continuously added, the white precipitate dissolved to form an aqueous solution of Na2Sn(OH)6, and the pH value of the solution was controlled above 12; then cobalt chloride solution was added under magnetic stirring to obtain a blue-purple suspension mixture; after stirring for 24 hours, the formed suspension was transferred to a 100 ml polytetrafluoroethylene-lined stainless steel autoclave and maintained at 180°C for 12 hours; after the autoclave was naturally cooled to room temperature, the precipitate obtained by suction was thoroughly washed several times with anhydrous ethanol and deionized water, and the precipitate was placed in a vacuum drying oven at 80°C and dried for 12 hours, and the precursor CoSn(OH)6 was obtained after grinding.

[0106] 3) Introducing Bi source by electrodeposition

[0107] Bi source was introduced on the conductive fluorine-doped tin oxide (FTO) coated glass substrate by electrodeposition. 8mmol Bi(NO3)3·5H2O was dissolved in 50mL aqueous solution containing 16mL acetic acid (99%) and 1.6mL concentrated HNO3 (70wt%) to prepare 0.2M bismuth precursor solution. A three-electrode electrolytic cell was constructed using a Pt counter electrode, a saturated Hg / Hg2SO4 reference electrode, and a cleaned FTO, and an external bias of 2.11V vs.Ref was applied for 1h; the obtained bismuth precursor film was rinsed with ultrapure water and dried naturally at room temperature.

[0108] 4) Introduce V source by spin coating and calcination

[0109] In order to convert the bismuth precursor film into BiVO4 film, the V source was introduced by spin coating. Isopropanol was used as a solvent to prepare a 0.05M vanadium acetylacetonate solution, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL of vanadium acetylacetonate solution was evenly added each time for spin coating, and a total of 3 spin coatings were performed; after drying at room temperature, annealing was performed at 450℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0110] 5) Spin coating to introduce CoSn(OH)6 and calcination

[0111] CoSn(OH)6 was also introduced by spin coating to complete the composite of CoSnO3 and BiVO4. The annealed film was rinsed with ultrapure water to remove excess V2O5 on the surface; 0.1MCoSn(OH)6 solution was prepared with ethanol as a solvent, and the spin coating parameters were set to a speed of 4000rpm, an acceleration of 800rpm / s, and a spin coating time of 30s. 50μL CoSn(OH)6 solution was evenly dripped for spin coating; after drying at room temperature, annealed at 300℃ in a muffle furnace at a heating rate of 5℃ / min for 2 hours.

[0112] Figure 1The scanning electron microscope morphology diagrams of Example 1 and Example 2 of the present invention are shown in Figure 1. CoSn(OH)6 powder samples were prepared by coprecipitation, and CoSnO3 / BiVO4 photoanode films were prepared on FTO conductive glass substrates by electrodeposition, spin coating and calcination. A BiVO4 blank control sample was prepared using the same film-making method. As shown in the figure, the BiVO4 film sample prepared on the FTO conductive glass substrate exhibits an amorphous morphology, with a rough surface but a consistent thickness. The nanocrystals are sintered together to form a relatively tight structure. It can be seen from the figure that the CoSnO3 obtained after calcination exhibits a uniform cubic morphology, with a particle size maintained at about 800nm, and can be evenly covered on the surface of the BiVO4 layer. The cross-sectional SEM diagram of CoSnO3 / BVO loaded on the FTO conductive glass substrate can clearly distinguish the CoSnO3 layer, the BiVO4 layer and the FTO layer, wherein the CoSnO3 cubes are relatively evenly embedded on the surface of the BiVO4 layer, and the thickness of the BiVO4 layer is maintained at about 267.5nm. Figure 2 This is the transmission electron microscopy phase image of Example 2. High-resolution transmission electron microscopy (HR-TEM) clearly shows that there are two obvious lattice spacings of 0.464nm and 0.216nm inside the image, which correspond to the (0 1 1) plane of monoclinic phase BiVO4 (PDF#14-0688) and the (1 1 2) plane of CoSnO3 (PDF#28-1236), respectively. This indicates that CoSnO3 and BiVO4 are successfully composited.

[0113] Figure 3The X-ray diffraction (XRD) patterns of the samples of Example 1 and Example 2 of the present invention show that in the coprecipitation process, the two samples with stirring times of 30 min and 10 h can both observe obvious peaks at 2Theta values ​​of 26.91°, 34.19° and 34.61°, which is consistent with the standard card of CoSnO3 of PDF#28-1236. However, in the powder sample with stirring time of 30 min, the peaks of the impurity phase of CoO and SnO2 can also be observed at the same time. This phenomenon is attributed to the incomplete formation of CoSnO3 in the coprecipitation process due to the too short stirring time. After the stirring time is extended to 10 h, there is a large broad peak in the range of 32-35°, which proves that amorphous CoSnO3 is formed, and no excessive impurity peaks are found, indicating that CoSnO3 close to pure phase is prepared. From the X-ray diffraction (XRD) spectrum of CoSnO3 / BVO loaded on a conductive glass substrate (FTO), it can be observed that there is no significant difference in the peak positions of the three catalyst samples, CoSnO3 / BVO and pure BVO, with controlled stirring time of 24h and 10h. They all contain impure peaks of Bi2O3 and SnO2 from FTO itself. The generation of the Bi2O3 impure peak is due to the fact that when the Bi source is introduced by electrodeposition and then the V source is introduced by spin coating, the two do not react fully. Some Bi sources do not contact the V source, resulting in the generation of Bi2O3 from the Bi source that does not react with the V source during the subsequent calcination process. The reason why there is no obvious difference in the peak positions of the three catalyst samples is that the amount of spin-coated CoSn(OH)6 is small, and the introduction of too much CoSnO3 will affect the light absorption performance of the composite catalyst.

[0114] Figure 4 The XPS spectra of the samples of Example 1 and Example 2 of the present invention are shown in Figure 1. From the overall spectra of the original BiVO4 and CoSnO3 / BVO samples, the characteristic peaks of Bi, V, and O contained in BiVO4 can be seen in both samples. The peaks of Co 2p, Sn 3d, and Bi 3p appear in the CoSnO3 / BVO sample, which also indicates the successful recombination of CoSnO3 and BiVO4. In the Sn 3d spectrum, the two Sn 3d peaks of CoSnO3 / BVO at 486.6 and 495 eV are 5 / 2 and Sn 3d 3 / 2 The peak confirmed Sn 4+ The Co 2p spectrum shows two fitting peaks at 780.7 and 796.5 eV, accompanied by two satellite peaks (785.4 and 802.3 eV), corresponding to the Co 2p 3 / 2 and Co 2p 1 / 2 As can be seen from the figure, the Bi(4f 5 / 2 ) and Bi(4f7 / 2 ) are located at 163.77 and 158.47 eV respectively; while for the CoSnO3 / BVO sample, these characteristic peaks shift slightly to the lower energy direction and appear at 163.96 and 158.59 eV respectively; in addition, the difference in the binding energy of V 2p between BiVO4 and CoSnO3 / BVO is negligible. In the O1s spectrum, in addition to the lattice oxygen, there are also oxygen vacancies in the CoSnO3 / BVO sample, which may be attributed to the oxygen vacancies formed by the extraction of oxygen from the lattice of the two oxygen-containing compounds during the formation of the CoSnO3 and BiVO4 composite catalyst during the calcination operation after spin coating of CoSn(OH)6.

[0115] Figure 5 For the photoelectrochemical tests of all embodiments of the present invention, a xenon lamp (100 mW cm -2 ) simulated the standard spectrum of the earth's surface (AM 1.5G), and measured the photoelectrochemical performance of the CoSnO3 / BiVO4 catalyst photoanode in 1M Na2CO3 electrolyte. For comparison, the photoelectrochemical activity of the original BiVO4 and the samples with stirring time of 10h, 30min, and 24h in the coprecipitation method were also studied. As shown in the figure, the photocurrent density of the original BiVO4 photoanode is relatively low (only 0.121mA cm at 1.59V vs.RHE). -2 ), while the composite CoSnO3 / BVO sample showed better photoelectric performance, with a photocurrent density of 3.47 mA cm under the same external bias potential. -2, the photocurrent density increased by about 28.68 times. The unique octahedral structure of perovskite structured metal oxides gives it excellent photoelectrochemical properties. It also has high specific surface area characteristics and pore structure. In the catalytic reaction process, it provides channels for the catalytic reaction substances to enter and the products to leave. The pore structure can also promote the diffusion and transmission of the reaction substances, thereby improving the efficiency of the catalytic reaction. The CoSnO3 powder prepared by the coprecipitation method has the characteristics of simple structure, high stability, and fast electron transfer rate. At the same time, CoSnO3, as a mixed transition metal oxide, has two different metal cations, because the atomic mixed matrix helps to regulate the internal stress of the electrode when the volume changes. More importantly, due to the different expansion coefficients of the two metal elements, the stability of the mixed transition metal oxide is better than that of the single metal transition metal oxide, and the activation energy barrier between different cations is reduced, thereby enhancing electron transfer. After the composite of CoSnO3 and BiVO4, the excellent visible light excitation ability of BiVO4 can be utilized, and the electron transport capacity of the photoelectrocatalytic material can be greatly improved through CoSnO3, reducing the recombination consumption of photogenerated carriers inside the catalytic material, so that more photogenerated carriers can participate in the redox reaction on the surface of the photoelectrocatalytic material. From the LSV curve in the figure, it can be clearly seen that the starting potential of CoSnO3 / BVO has been greatly reduced compared with pure BVO, and the electrode reaction on the CoSnO3 / BVO composite material can occur faster; at the same time, the It curve in the figure shows that the CoSnO3 / BVO composite material also obtains a larger photocurrent density under the same bias, which shows that the composite material can greatly improve its photoelectrocatalytic performance; from the EIS graph, it can be seen that the addition of CoSnO3 makes the electron transmission rate on the catalyst surface faster, the photogenerated electrons and photogenerated holes can be effectively separated and transferred on the catalyst surface, the charge transfer impedance is low, and the charge transfer efficiency between electrons and reactants is high, thereby promoting the photoelectrocatalytic reaction. The stirring time in the coprecipitation method is one of the important factors affecting its crystal growth, which will significantly affect the nucleation and growth process of the crystal, thereby affecting the size and morphology of the final particles. Setting the experimental conditions to stir for 10 hours can provide ideal conditions for crystal growth, which not only ensures sufficient nucleation number and crystal uniformity, but also avoids agglomeration or excessive crystallization caused by too long stirring. On the one hand, too short stirring time may not be enough to form uniformly distributed crystals, and on the other hand, other impurities may appear in the sample due to incomplete reaction, thus affecting the catalytic performance of the catalyst. Too long stirring time may also cause the crystal size to be too small or agglomerate, which in turn reduces its photoelectric performance.

[0116] Figure 6The graph of the photoelectrocatalytic Faraday efficiency and hydrogen peroxide yield of Example 2 of the present invention shows that the catalytic performance of the CoSnO3 / BiVO4 photoelectrocatalytic anode remains good when the test is continued for more than 120 min, and the maximum yield during the test is 0.449 μmol min -1 cm -2 , the Faraday efficiency reaches 79.23%.

[0117] In summary, the present invention prepares CoSn(OH)6 powder by co-precipitation and hydrothermal method, and prepares dense and uniform BiVO4 catalyst layer and CoSnO3 catalyst layer on the surface of FTO substrate by combining electrodeposition and spin coating, so as to form a composite photoelectrocatalytic anode material with excellent catalytic activity and strong corrosion resistance. After multiple photoelectrochemical tests, the catalyst does not obviously fall off and has good light transmittance. Therefore, the photoelectrocatalyst prepared by the present invention can effectively improve the photocurrent of the original BiVO4 itself, and can have high selectivity and high yield in the reaction of preparing hydrogen peroxide by two-electron water oxidation, thereby effectively reducing the cost of photoelectrocatalytic preparation of hydrogen peroxide and promoting the popularization and application of this technology.

[0118] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a CoSnO3 / BiVO4 photoanode, characterized in that: The following steps are involved: Step s1, cleaning the conductive substrate to remove impurities on the surface of the conductive substrate; Step s2, adding solution A to the Co source and Sn source solutions by co-precipitation method to prepare catalyst slurry, and then transferring the slurry to a chemical reaction device for hydrothermal preparation of CoSn(OH)6 powder; Step s3, dissolving a Bi source in solvent B to prepare a Bi precursor solution, and introducing the Bi source onto the conductive substrate treated in step s1 by electrodeposition; Step s4, dissolving the V source in solvent C, and then introducing the V source by spin coating on the conductive substrate treated in step s3 using a spin coating device and heating and calcining in a high temperature heating device to prepare a photoanode BiVO4 layer; Step s5, introducing CoSn(OH)6 on the conductive substrate treated in step s4 by spin coating using a spin coating device and heating and calcining in a high temperature heating device to finally obtain a CoSnO3 / BiVO4 photoelectrocatalytic electrode; The solution A comprises: one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide; The solvent B includes: one or more of glacial acetic acid, nitric acid, sulfuric acid, hydrochloric acid, oxalic acid, and deionized water; The solvent C includes one or more of ethylene glycol, ethanol, methanol, isopropanol, and deionized water.

2. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: The Co source includes: one or more of cobalt chloride hexahydrate, cobalt sulfate heptahydrate, hydrated cobalt carbonate, and cobalt nitrate hexahydrate; the Sn source includes: one or more of tin chloride dihydrate, anhydrous stannous chloride, tin sulfate, stannous sulfate, stannous carbonate, and stannous oxalate; the Bi source includes: one or more of bismuth nitrate pentahydrate, bismuth subcarbonate dihydrate, and bismuth sulfate; the V source includes: one or more of vanadium acetylacetonate, ammonium metavanadate, and vanadium pentoxide.

3. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: The conductive substrate includes: fluorine-doped silicon dioxide conductive glass FTO, indium tin oxide transparent conductive film glass ITO, and a stainless steel plate.

4. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: In step s2, the chemical reaction apparatus includes: a reactor, an autoclave, a stirred reactor, a continuous flow reactor, a microreactor, a batch reactor, a fixed bed reactor, and a fluidized bed reactor; In step s4 and step s5, the high temperature heating device includes: a muffle furnace, a tube furnace, a box furnace, a vacuum furnace, an atmosphere furnace, a resistance furnace, and an induction furnace; In step s4 and step s5, the spin coating device includes: a glue spreader, a spin coater, a glue spinner, a spin coater, a spin film coater, a spin coating machine, a spin coater, and a vacuum coating machine.

5. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: In the step s1, the cleaning step includes: using deionized water, acetone, isopropanol and ethanol in sequence to ultrasonically bathe the conductive substrate for 5 to 20 minutes; the sizes of the conductive substrate include: 1cm*1cm, 1cm*2cm, 2cm*2cm, 2cm*3cm.

6. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: In the step s2, the stirring speed of the coprecipitation method is 100-800 rpm, and the stirring time is 10 min-24 h; the hydrothermal time is 6-18 h, and the hydrothermal temperature is 120-200° C.

7. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: In the step s3, the electrodeposition conditions include: applying an external bias voltage of 0.5V to 2.5V vs. Ref for 10min to 2h; Among them, in the three electrodes of electrodeposition, the counter electrode includes: one of a carbon counter electrode and a platinum counter electrode; the reference electrode includes: one of a saturated Hg / Hg2SO4 electrode, a saturated Ag / AgCl electrode, a saturated Hg / HgO electrode, and a calomel electrode; and the working electrode is a conductive substrate.

8. The method for preparing a CoSnO3 / BiVO4 photoanode according to claim 1, characterized in that: In step s4, the temperature of the high temperature heating device is set to 350-500° C., the heating rate is 5-10° C. / min, and the calcination time is 1-4 hours; In the step s5, the temperature of the high temperature heating device is set to 250-400° C., the heating rate is 5-10° C. / min, and the calcination time is 1-4 hours.

9. A CoSnO3 / BiVO4 photoanode, characterized in that: The CoSnO3 / BiVO4 photoanode is prepared by the preparation method of the CoSnO3 / BiVO4 photoanode according to any one of claims 1 to 8.

10. Use of a CoSnO3 / BiVO4 photoanode in the preparation of hydrogen peroxide, characterized in that: The application uses the CoSnO3 / BiVO4 photoanode in claim 9 to prepare hydrogen peroxide.

Citation Information

Patent Citations

  • Method for preparing cobalt oxide / bismuth vanadate composite material by spin-coating and calcining

    CN110227478A

  • Semiconductor anode material for hydrogen peroxide preparation by photoelectrocatalysis and preparation method thereof

    CN110468428A

  • Synthesis method of BiVO4-Ni / Co3O4 heterojunction and application of BiVO4-Ni / Co3O4 heterojunction to photoelectrochemical hydrolysis

    CN111569896A

  • SnOx / BiVO4 electrode, preparation method thereof and application of SnOx / BiVO4 electrode to photoelectrocatalytic hydrogen peroxide synthesis

    CN111979561A

  • Cobalt-lanthanum co-doped visible light response BiVO4 photoelectrode and preparation method thereof

    CN114411168A